Pengaruh Kepemilikan Manajerial, Profitabilitas dan Leverage terhadap Kebijakan Dividen dengan Likuiditas sebagai Variabel Moderating pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2017-2021 - Armayini, Cici; Minan, H. Kersna (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This study aims to determine the effect of managerial ownership, profitability and leverage on dividend policy in manufacturing companies listed on the Indonesia Stock Exchange for the 2017-2021 period. Dividend policy is needed in determining the distribution of dividends in a company. Dividend policy concerns the company's decision to determine the use of the profits earned by the company, namely whether the profits will be distributed to shareholders or used as retained earnings to be reinvested in the company. Shareholders certainly hope to get large dividends, but the company has logical considerations because the company must think about the survival and growth of the company in the future. The population in this study were all manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021, with a purposive sampling technique so that 31 companies were obtained for 5 years of observation. The data analysis used in this research is moderated regression analysis. The results of this study indicate that Managerial Ownership, Profitability and Leverage have a significant effect on Dividend Policy in Manufacturing companies listed on the IDX for the 2017-2021 period. Liquidity cannot moderate Managerial Ownership, Profitability and Leverage on Dividend Policy in Manufacturing companies listed on the IDX for the 2017–2021 period. Keywords: Managerial Ownership, Profitability, Leverage, Liquidity and Dividend Policy.